Analisis Implementasi Kerja Sama Filipina dan Amerika Serikat dalam Penanggulangan Aksi Terorisme di Filipina - Wardani, Linda Ayu; Utomo, Tri Cahyo (Journal of International Relations, 2018)
Terrorist acts in the Philippines come from terrorist groups such as MNLF, MILF, JI, NPA, and ASG, who have existed long before the events of 9/11 that hit United States. Not only are they created a number of losses to the Philippines but also to the United States. Military or non-military counter-terrorism cooperation with the United States is one of the Philippines' efforts to overcome the terror of these groups. This study aims to determine the implementation of counter-terrorism cooperation between the Philippines and the United States in dealing with act of terrorism in the Philippines from 2010-2016. This research was analyzed by using the framework of liberalism. This research was done by using qualitative research method with descriptive research type. The results of this study indicate that counter-terrorism cooperation between the Philippines and the United States has been quite successful as evidenced by the approval of military cooperation with the establishment of the JSOTF-P program to train AFP and PNP SAF, then ATA programs to train PNP SAF. In addition, from non-military cooperation, the humanitarian and development assistance from USAID is also used to build Mindanao communities, especially those affected by act of terrorism. However, the cooperation has not completely reduced the high number of terrorist attacks and captured all the most wanted terrorists in the Philippines.